First case of endometrial cancer after yolk sac tumor in a patient with Li-Fraumeni syndrome - Qiu-Lin Ye; Yue Qi; Juan-Juan Liu; Yue-Xin Hu; Yuan Lv; Bei Lin (BMC Women's Health, 2023)
Abstract Background Li-Fraumeni syndrome (LFS) is a rare autosomal dominant disease with high penetrance caused by a germline variant of TP53 gene. We report the first case of endometrial cancer after yolk sac tumor with LFS. Case presentation The presented female patient underwent right adnexectomy at age 23 because of a yolk sac tumor of the ovary. At the age of 27, the patient was diagnosed with endometrial adenocarcinoma, received cytoreductive surgery and chemotherapy. Given that her personal cancer history along with a strong family history of cancer, her father passing away from lung cancer at age 48 and her grandmother dying of ovarian cancer at age 50, the patient was referred for genetic counseling and testing. Genetic screening revealed a heterozygous pathogenic TP53 c.844C > T, p.( R282 W) with NM_000546.5 variant, a class 5 (C5) variant. This is the first reported case of a yolk sac tumor accompanied by subsequent endometrial cancer that is associated with LFS. Conclusions We reported a first case of an endometrial cancer after yolk sac tumor patient with a tumor family history of harboring the germline TP53 pathogenic variation which expanded types of tumor that can be presented in patients with LFS. This case highlights the importance of genetic testing for patients with malignant tumors, as well as patients with a family history of malignant tumors. And our case highlights the necessity of screening for gynecologic tumor in LFS patients.